Numerical analysis of natural convection in an inclined trapezoidal enclosure filled with a porous medium - Varol, Yasin; Öztop, Hakan Fehmi; Pop, Ioan (Elsevier France-Editions Scientifiques Medicales Elsevier, 2008)
A theoretical study of buoyancy-driven flow and heat transfer in an inclined trapezoidal enclosure filled with a fluid-saturated porous medium heated and cooled from inclined walls has been performed in this paper. The governing non-dimensional equations were solved numerically using a finite-difference method. The effective governing parameters are: the orientation or inclination angle of the trapezoidal enclosure phi, which varies between 0 degrees and 180 degrees, the Rayleigh number Ra, which varies between 100 and 1000, the side wall inclination angle theta(s) and the aspect ratio A. The side wall inclination parameter theta(s) is chosen as 67 degrees, 72 degrees and 81 degrees and the calculations are tested for two different values of A = 0.5 and 1.0. Streamlines, isotherms, Nusselt number and flow strength are presented for these values of the governing parameters. The obtained results show that inclination angle phi is more influential on heat transfer and flow strength than that of the side wall inclination angle theta(s). It is also found that a Benard regime occurs around phi = 90, which depends on the inclination of the side wall, Rayleigh number and aspect ratio. 2007 Elsevier Masson SAS. All rights reserved.
Keywords: trapezoidal enclosure; porous medium; natural convection; numerical solution